PARSIMONIOUS MACHINE LEARNING MODELS IN REQUIREMENTS ELICITATION TECHNIQUES SELECTION - Solovei, Olga; Gobov, Denys (Vestnik Nacionalʹnogo tehničeskogo universiteta "HPI". Seriâ Sistemnyj analiz, upravlenie i informacionnye tehnologii (Online), 2023)
The subject of research in the article is machine learning algorithms used for requirement elicitation technique selection. The goal of the work is to build effective parsimonious machine learning models to predict the using particular elicitation techniques in IT projects that allow using as few predictor variables as possible without a significant deterioration in the prediction quality. The following tasks are solved in the article: design an algorithm to build parsimonious machine learning candidate models for requirement elicitation technique selection based on gathered information on practitioners' experience, assess parsimonious machine learning model accuracy, and design an algorithm for the best candidate model selection. The following methods are used: algorithm theory, statistics theory, sampling techniques, data modeling theory, and science experiments. The following results were obtained: 1) parsimonious machine learning candidate models were built for the requirement elicitation technique selection. They included less number of features that helps in the future to avoid overfitting problems associated with the best-fit models; 2) according to the proposed algorithm for best candidate selection – a single parsimonious model with satisfied performance was chosen. Conclusion: An algorithm is proposed to build parsimonious candidate models for requirement elicitation technique selection that avoids the overfitting problem. The algorithm for the best candidate model selection identifies when a parsimonious model's performance is degraded and decides on the suitable model's selection. Both proposed algorithms were successfully tested with four datasets and can be proposed for their extensions to others.